Cosatu after 40: Introduction: Founding principles, present realities and future challenges - Jacobs, Mario; Godfrey, Shane; Macun, Ian (New Agenda: SA Journal of Social and Economic Policy, 2026)
COSATU, South Africa’s storied federation of trade unions, with its affiliates, played a critical role in the defeat of apartheid and in the construction of new modes of industrial relations – and politics – after 1994. Forty years old in 2025, COSATU’s industrial unionism model is the focus of this fine-grained analysis by SHANE GODFREY, MARIO JACOBS and IAN MACUN. This special focus provides a context for a discussion on the state of unions in South Africa today. Its focus moves the debate beyond recognition of the impact of economic liberalisation, features of corruption and authoritarianism, and the changing social composition of the union membership to consider what the future could hold for the way COSATU and its affiliates are structured in a difficult new world.